ANALYSIS OF LISTENING ENGLISH SONGS ON STUDENT'S VOCABULARY LEARNING - Kristantri Suciati; Enci Zarkasih (Lingua, 2021)
Listening is a skill that is acquired from birth. Meanwhile, listening to English songs is becoming a trend among young students. The purpose of this research is To analyze the English songs to enhance student's vocabulary learning at As-Syafi'iyah Islamic Senior High School 02 academic year 2020/2021. Therefore the research question is: How is the role of English songs to enhance student's vocabulary learning at As-Syafi'iyah Islamic Senior High School? The research was conducted in August - November 2020. The research sample was 6 students of class X SMA As-Syafi'iyah 02 Bekasi academic year 2020/2021 who were selected based on a purposive sample. The research instrument uses an interview. The results of this study found that English songs have a role in the vocabulary learning of students. Listening to English songs not only makes them relax and enjoy but can also enrich their vocabulary and tell them how to pronounce a word in English.